Bevacizumab plus chemotherapy in nonsquamous non‐small cell lung cancer patients with malignant pleural effusion uncontrolled by tube drainage or pleurodesis: A phase II study North East Japan Study group trial NEJ013B. Issue 7 (18th May 2020) - Noro, Rintaro; Kobayashi, Kunihiko; Usuki, Jiro; Yomota, Makiko; Nishitsuji, Masaru; Shimokawa, Tsuneo; Ando, Masahiro; Hino, Mitsunori; Hagiwara, Koichi; Miyanaga, Akihiko; Seike, Masahiro; Kubota, Kaoru; et al.
Abstract : Background: Pleurodesis is the standard of care for non‐small cell lung cancer (NSCLC) patients with symptomatic malignant pleural effusion (MPE). However, there is no standard management for MPE uncontrolled by pleurodesis. Most patients with unsuccessful MPE control are unable to receive effective chemotherapy. Vascular endothelial growth factor (VEGF) plays an important role in the pathogenesis of MPE. This multicenter, phase II study investigated the effects of bevacizumab plus chemotherapy in nonsquamous NSCLC patients with unsuccessful management of MPE. Methods: Nonsquamous NSCLC patients with MPE following unsuccessful tube drainage or pleurodesis received bevacizumab (15 mg/kg) plus chemotherapy every three weeks. The primary endpoint was pleural effusion control rate (PECR), defined as the percentage of patients without reaccumulation of MPE at eight weeks. Secondary endpoints included pleural progression‐free survival (PPFS), safety, and quality of life (QoL). Results: A total of 20 patients (median age: 69 years; 14 males; 20 adenocarcinomas; six epidermal growth factor receptor mutations) were enrolled in nine centers. The PECR was 80% and the primary end point was met. The PPFS and the overall survival (OS) were 16.6 months and 19.6 months, respectively. Patients with high levels of VEGF in the MPE had shorter PPFS ( P = 0.010) and OS ( P = 0.002). Toxicities of grade ≥ 3 included neutropenia (50%), thrombocytopenia (10%), proteinuria (10%), and hypertension (2%). The cognitive QoL score improved after treatment. Conclusions: Bevacizumab plus chemotherapy is highly effective with acceptable toxicities in nonsquamous NSCLC patients with uncontrolled MPE, and should be considered as a standard therapy in this setting. Key points: Significant findings of the study: Bevacizumab plus chemotherapy is highly effective with acceptable toxicities in nonsquamous NSCLC patients with uncontrolled MPE. What this study adds: Bevacizumab plus chemotherapy should be considered as a standard treatment option for patients with uncontrolled MPE. Clinical trial registration: UMIN000006868 was a phase II study of efficacy of bevacizumab plus chemotherapy for the management of malignant pleural effusion (MPE) in nonsquamous non‐small cell lung cancer patients with MPE unsuccessfully controlled by tube drainage or pleurodesis (North East Japan Study Group Trial NEJ‐013B) (http://umin.sc.jp/ctr/ ).